Fathers' rejection sensitivity: Links with fathers' and children's social information processing. - Sher‐Censor, Efrat; Gur‐Yaish, Nurit; Polachek, Esther; Ziv, Yair (Family Relations (John Wiley & Sons, Inc.), 2025)
Objective: Joining efforts to reveal how fathers affect their children's social competence, we examined whether fathers' rejection sensitivity was associated with biases in their children's social information processing. We also explored whether this link was indirect via biases in fathers' social information processing of their children's peer interactions and, in particular, fathers' behavioral responses. Background: Children's social information processing biases predict their social competence and well‐being. Studies have explored how mothers' rejection sensitivity may impact children's social information processing. Yet, little is known about the role of fathers in this context. Method: Participants were 85 fathers living in Israel (68.24% Jewish; 31.76% Arab) and their kindergarten children (55.29% female; MChild age in months = 68.70, SD = 5.59). Fathers completed the Adult Rejection Sensitivity Questionnaire and reported their attributions, emotions, and likely behaviors in ambiguous hypothetical scenarios that might suggest a rejection of their child by peers using the Peer Rejection Scenarios measure. Children were interviewed using the Social Information Processing Interview–Preschool Version, tapping hypothetical peer interactions. Results: Fathers' rejection sensitivity was indirectly related to children's generation of maladaptive responses to ambiguous peer interactions through fathers' reports of their more negative emotions and overinvolved behavioral responses. Conclusion: Results underscore the role of fathers' rejection sensitivity and emotional and behavioral responses in children's social information processing. Implications: The study points to the need to consider paternal rejection sensitivity in research and interventions focused on promoting children's social competence.